Effects of Broussonetia papyrifera (L.) L'Hér. ex Vent. fruits water extract on hippocampal neurogenesis in the treatment of APP/PS1 transgenic mice - Yan, Yu-hui; Huang, Zi-han; Xiong, Qing-ping; Song, Yue-wen; Li, Si-yang; Yang, Bao-wei; Sun, Lan; Zhang, Meng-yuan; Ji, Yu (Frontiers in Pharmacology, 2022)
Background: Adult neurogenesis plays an important role in repairing damaged neurons and improving cognitive impairment in Alzheimer’s disease (AD). Broussonetia papyrifera (L.) L'Hér. ex Vent. fruits (BL), a traditional Chinese medicine for tonifying the kidney, has been reported to improve cognitive function in AD mice, but the underlying mechanisms have not been clearly illuminated. This study aimed to provide an overview of the differential compounds in the brain of APP/PS1 mice after BL water extract (BLWE) treatment through metabolomics technology and to elucidate whether the therapeutic effect and mechanism are through the enhancement of neurogenesis. Methods: APP/PS1 transgenic mice were treated with different doses of BLWE. After 6 weeks of intragastric injection, the therapeutic effects of BLWE on APP/PS1 transgenic mice were determined by the Morris water maze test, immunohistochemistry, hematoxylin & eosin and Nissl staining, enzyme-linked immunosorbent assay and terminal deoxynucleotidyl transferase dUTP nick end labeling staining. Subsequently, metabolomics technology was used to analyze the regulatory effect of BLWE on differential compounds in the brain of APP/PS1 mice, and on this basis, its molecular mechanism of BLWE was screened. Finally, the protein expression of the Wnt/β-catenin signaling pathway was detected by Western blotting. Results: After BLWE treatment, the learning and memory function of APP/PS1 mice were significantly improved, which was related to the increase in the number of Nestin+/BrdU+ and NeuN+¬/BrdU+ cells, and the decrease in the number of apoptotic cells in the hippocampus. BLWE treatment could also up-regulate the expression of synapse-associated proteins. Moreover, BLWE could modulate endogenous metabolic compounds in the brains of AD mice, including N-acetyl-aspartate, glutamine, etc. Furthermore, BLWE inhibited the phosphorylation of Tyr216-GSK-3β and β-catenin protein while increased CyclinD1 protein expression. Conclusions: We demonstrated that BLWE can enhance neural stem cells proliferation and improve neurogenesis, thereby efficiently repairing damaged neurons in the hippocampus and ameliorating cognitive impairment in APP/PS1 transgenic mice. The mechanism is at least partly through activating the Wnt/β-catenin signaling pathway.